2014
DOI: 10.1007/s00429-014-0795-8
|View full text |Cite
|
Sign up to set email alerts
|

Toward neurobiological characterization of functional homogeneity in the human cortex: regional variation, morphological association and functional covariance network organization

Abstract: Local functional homogeneity of the human cortex indicates the boundaries between functionally heterogeneous regions and varies remarkably across the cortical mantle. It is unclear whether these variations have the neurobiological and structural basis. We employed structural and resting-state functional magnetic resonance imaging scans from 482 healthy subjects and computed the vertex-wise regional homogeneity of low-frequency fluctuations (2dReHo) and five measures of cortical morphology. We then used these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 140 publications
3
112
0
2
Order By: Relevance
“…Changes in cortical volume or thickness may be driven in part by alterations at the synaptic level, such as synaptic and neuronal pruning or regeneration processes, which may be reflected in patterns of functional connectivity. Additionally, the biological implications of 2dReHo indicate that functional segregation and integration within brain regions may be linked to corresponding anatomical variation (Jiang et al, 2014). In light of these findings, we concluded that local functional homogeneity of verbal creative thinking has neurobiological relevance and an anatomical basis.…”
Section: Variations In Structure and Function Contribute To Verbal Crmentioning
confidence: 70%
See 3 more Smart Citations
“…Changes in cortical volume or thickness may be driven in part by alterations at the synaptic level, such as synaptic and neuronal pruning or regeneration processes, which may be reflected in patterns of functional connectivity. Additionally, the biological implications of 2dReHo indicate that functional segregation and integration within brain regions may be linked to corresponding anatomical variation (Jiang et al, 2014). In light of these findings, we concluded that local functional homogeneity of verbal creative thinking has neurobiological relevance and an anatomical basis.…”
Section: Variations In Structure and Function Contribute To Verbal Crmentioning
confidence: 70%
“…curve is the maximum and minimum bending of the cortical surface at a given vertex; and folding index is a metric that quantifies the amount of folding overall on a surface (Jiang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has applied these regional metrics to index developmental and aging phenomena in the connectome, as well as to index inter-individual variation in behavior and cognition (Mennes et al, 2011). One caveat is that, while potentially valuable for biomarker development, the neurobiological meaning of these regional measures is yet to be determined (see an initial effort in Jiang et al, 2014). …”
Section: Section 4: Analytic Models and Considerationsmentioning
confidence: 99%